Climate Change and Carbon Emission Trading - Nungula, Emmanuely Z.; Chappa, Luciana R.; Ngaiza, Vedasto V.; Msangi, Grace S.; Dlamini, Jerry C.; Saeed, Amjad; Mwadalu, Riziki; Raza, Muhammad A.; Soratto, Rogério P. [UNESP]; Rezaei-Chiyaneh, Esmaeil; Nasar, Jamal; Gitari, Harun I. (Springer Nature, 2025)
Ecological, social, and economic challenges are driving the global phenomenon known as climate change. Research indicates that anthropogenic activities, such as agricultural production, industrial activities, and transportation (which rely on fossil fuels), as well as the use of natural gases that release greenhouse gases, are the major causes of these problems that impact the Earth’s surface population. This chapter focuses on discussing the concept of climate change and its causes, considering both natural and anthropogenic factors. It also highlights the contributions of the agricultural sector—such as fertilizer application, livestock farming, land use, and chemical use—to global climate change, which is a key issue in the global dialogue. Evidence of climate variability, including desertification, sea level rise, increasing temperatures and wildfires, rainfall variability, and the melting of ice and glaciers, is presented as an indicator of these changes. The chapter further examines the impacts of climate change on agriculture, water resources, biodiversity, and public health, and explores mitigation and adaptation strategies to cope with its effects. Additionally, it explains the concept of carbon emission trading, including the international emissions trading framework and its associated challenges.